(untitled) (Journal of EAHIL, 2017)
The Special Interest Group (SIG) on MeSH translation met on June 11 and gathered a section of the 14th EAHIL Conference participants from Belgium, the Dutch Caribbean, Netherlands, Norway, Romania, Sweden, Switzerland, United Kingdom, and of course Italy. The idea of meeting for SIGs during the Conference and not on the day/days before, when CE courses are usually held, was very successful and we gathered over twenty people interested in MeSH translation.